2022
DOI: 10.3390/cimb44120424
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of 6-Gingerol in Prevention of Colon Cancer Induced by Azoxymethane through the Modulation of Antioxidant Potential and Inflammation

Abstract: A polyphenolic component of ginger, 6-gingerol, is widely reported to possess antioxidant, anti-inflammatory and anticancer activities. In the current study, it was aimed to investigate the anticancer effects of 6-gingerol (6-Gin) on azoxymethane (AOM)-induced colon cancer in rats. The results reveal that 6-Gin treatment significantly improves the antioxidant status disturbed by AOM intoxication. The 6-Gin treatment animal group showed enhanced activity of catalase (CAT) (46.6 ± 6.4 vs. 23.3 ± 4.3 U/mg protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The study conducted by Aloliqi et al showed that the compound 6-gingerol can reduce the development of colon cancer produced by AOM. This effect is achieved by reducing oxidative stress and inflammation, preserving the structural integrity of the colon tissue and maintaining the expression of the PTEN protein [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Aloliqi et al showed that the compound 6-gingerol can reduce the development of colon cancer produced by AOM. This effect is achieved by reducing oxidative stress and inflammation, preserving the structural integrity of the colon tissue and maintaining the expression of the PTEN protein [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to induce apoptosis and suppress angiogenesis. Gingerol has also demonstrated the ability to modulate various signaling pathways involved in cancer development and progression [434][435][436]. Furthermore, 6-gingerol has also been studied as a potential anticancer agent against skin cancers.…”
Section: Other Phenolic Compoundsmentioning
confidence: 99%
“…The bioactive components 6gingerol and 6-shogaol have a comparable chemical structure which is more profitable, be that as it may, 6-shogaol incorporates a more grounded dynamic control. Some ponders have appeared that 6-shogaol has more prominent viability than 6-gingerol, such as antioxidant action [3,[6][7][8], anti-inflammation activity [3,9,10], effect of anti-platelet aggregation [11], prevention of muscle contraction [12], prevention of colorectal cancer [13], ovarium cancer [14,15], breast cancer [16], and lung cancer [17,18]. The advancement of the 6 shogaol extraction handle coming about from the change of 6-gingerol from ginger mash has been carried out, including: extraction through a soxhletation device, subcritical water extraction [19], subcritical fluid extraction [20], hydrotropic extraction [21], microwave extraction [22], enzymatic extraction [23], ultrasonic extraction [24,25], and ionic liquid extraction [26].…”
Section: Introductionmentioning
confidence: 99%